Committing Murder and Punishment in US Criminal Law - Dr. Sepideh Sehat (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Intentional homicide, as defined in the custom of nations, is the unlawful killing of another human being with intent (or malice in the past), and this generally distinguishes premeditated murder from other forms of death. Because the loss of a human being imposes great grief on those close to the victim, as well as the fact that committing a murder torments the victim forever, most societies consider it a very serious crime. The most severe punishment is usually given to a murder suspect sentenced to life imprisonment or even the death penalty for such an act. A person who commits murder is called a murderer, and punishments in the United States of America vary from state to state, as outlined below. In the United States Maritime and Territorial Jurisdiction, anyone who commits first-degree premeditated murder will be sentenced to death or life imprisonment. Anyone who commits second-degree premeditated murder must be sentenced to long or life in prison. This article examines premeditated murder and how it is punished in US criminal law.